Equilibrium and kinetic studies on removal of phenolic compounds using activated carbon coated monolith - Teoh, Yi Peng (2014)
Activated carbon coated monolith (ACCM) was prepared by dipcoating method using a polymer mixture (furfuryl alcohol, and poly ethylene glycol). The adsorptive performance of phenol, 4-chlorophenol (4-CP), 2,4-dichlorophenol (2,4-DCP) onto the ACCM was comparatively evaluated by batch mode. Experiments were carried out at varying pH, contact time, initial adsorbate concentration and reaction temperature. Regeneration performance of ACCM was also assessed. This study showed an optimum adsorption for 2,4-DCP, followed by 4-CP, and phenol at pH 5.The adsorption equilibrium time for phenol, 4-CP, 2,4-DCP were 600 min, 500 min,and 400 min, respectively. The equilibrium adsorption capacity were increased 50.3 -62.9 mg/g (phenol), 88.9 - 111.5 mg/g (4-CP), and 89.9 - 117.5 mg/g (2,4-DCP),respectively at an increasing initial concentration of 400 – 600 mg/L. The adsorption was monolayer as depicted by linear and non-linear isotherm models. The adsorption kinetics was best represented by the pseudo-second order kinetics model. The adsorption capacity increases with increasing reaction temperature from 30 to 50oC,showing an endothermic process. Excellent recovery of phenol was observed during regeneration using ethanol, which showed an 81% efficiency after four consecutive cycles.